GAMBARAN PENGETAHUAN PEMULUNG TERHADAP ASPEK KESEHATAN KESELAMATAN KERJA (K3) DALAM PENGELOLAAN SAMPAH DI TEMPAT PEMBUANGAN SEMENTARA (TPS) KOTA PEKANBARU - Intan Komala Sari; Miftah Azrin; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTScavengers are workers who collect and sort solid waste that has value as recyclable materials. Scavengers have high risk factors to get disease and job accidents, but very limited research review about that. The aims of this research are to identify respondense characteristics and to describe knowledge of among scavengers about aspect of Occupational Health and Safety (OHS) at Temporary Disposal (TPS) Pekanbaru City. The methodology is descriptive study and used primary data by collecting direct interviews and giving questioners to 24 scavangers at 6 Temporary Disposal (TPS) Pekanbaru City. The accidental sampling technique is used in this research. The results show that characters of scavengers are dominated by females (54%), whose age between 26-45 years old (58%), and primary school graduates (29%), with working pattern up to <9 hour/day (71%) and most of respondense have enough category about aspect of Occupational Health and Safety (OHS).Key words : Scavengers, knowledge, occupational health and safety (OHS), temporary disposal (TPS).